2022
DOI: 10.3390/endocrines3010012
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome and Premenstrual Dysphoric Disorder as Centrally Based Disorders

Abstract: Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) encompass a variety of symptoms that occur during the luteal phase of the menstrual cycle and impair daily life activities and relationships. Depending on the type and severity of physical, emotional or behavioral symptoms, women of reproductive age followed for at least two prospective menstrual cycles may receive one of the two diagnoses. PMDD is the most severe form of PMS, predominantly characterized by emotional and behavioral symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 102 publications
0
7
0
2
Order By: Relevance
“…The factors confirmed to be the common associated factors for PMS and PMDD in the literature were considered when determining the inclusion and exclusion criteria for the participants. 1,3,9 In this way, it was aimed to focus on associated factors that are not commonly known.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors confirmed to be the common associated factors for PMS and PMDD in the literature were considered when determining the inclusion and exclusion criteria for the participants. 1,3,9 In this way, it was aimed to focus on associated factors that are not commonly known.…”
Section: Methodsmentioning
confidence: 99%
“…However, prevalence rates vary widely in different studies and countries depending on the characteristics of participants, personal attitudes, lifestyle, stressors, socio-cultural factors, environmental conditions, and different diagnostic criteria. [3][4][5] Although the meanings attributed to menstruation vary between societies, it is reported that there are many taboos and myths related to this period, especially in low and middle-income countries. Women who faced negative attitudes experience body dysfunction and perceive themselves as "dirty" and as a result, isolate themselves in their work/school and social lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, в публикациях отмечены следующие явления, возможно, приводящие к развитию ПМС и ПМДР: генетическая теория о полиморфизме генов усвоения и метаболизма триптофана. Результатом такого полиморфизма является низкий уровень серотонина с вытекающими симптомами психоэмоциональных проблем [10]. Заслуживающими внимания являются и другие нейроэндокринные теории: снижение активности рецепторов дофамина, пульсовое ночное повышение пролактина, «неправильное» восприятие прогестерона и его метаболитов в ЦНС, а также длительная дизадаптация к стрессу [10][11][12][13].…”
Section: таблица 5 исходные данные и динамика изменений гастроинтести...unclassified
“…Современные подходы к терапии ПМС/ПМДР ориентированы на подавление овуляции с помощью комбинированных гормональных контрацептивов, что особенно Как же в такой ситуации проявляет свои свойства Vitex Agnus Castus? Одним из первых хорошо изученных и описанных свойств этого растения является снижение уровня пролактина по дофаминергическому механизму (D 2 ) [10,11]. А как проявляется лечебный эффект при нормальных показателях пролактина?…”
Section: таблица 5 исходные данные и динамика изменений гастроинтести...unclassified